The N Terminus of Adhesion G Protein–Coupled Receptor GPR126/ADGRG6 as Allosteric Force Integrator - Mitgau, Jakob; Franke, Julius; Schinner, Camilla; Stephan, Gabriele; Berndt, Sandra; Placantonakis, Dimitris G.; Kalwa, Hermann; Spindler, Volker; Wilde, Caroline; Liebscher, Ines (Frontiers in Cell and Developmental Biology, 2022)
The adhesion G protein-coupled receptor (aGPCR) GPR126/ADGRG6 plays an important role in several physiological functions, such as myelination or peripheral nerve repair. This renders the receptor an attractive pharmacological target. GPR126 is a mechano-sensor that translates binding of extracellular matrix (ECM) molecules to its N terminus into a metabotropic intracellular signal. To date, the structural requirements and the character of the forces needed for this ECM-mediated receptor activation are largely unknown. In this study we provide this information by combining classic second messenger detection with single cell atomic force microscopy. We establish a monoclonal antibody targeting the N terminus to stimulate GPR126 and compare it to the activation through its known ECM ligands collagen IV and laminin 211. As each ligand uses a distinct mode of action, the N terminus can be regarded as an allosteric module that can fine-tune receptor activation in a context-specific manner.